Fortran 90 for engineers - Etter, Delores M. (Benjamin/Cummings, 1995)
Solving problems with Fortran 90. Arithmetic computations and simple programs. Control constructs. Engineering and scientific data files. Array processing. External procedures. Additional data types. An introduction to pointers.